Flood Damage Assessment on Rice Field: Case Study for Cambodia - Ket, Dydarong; Suttinon, Pongsak (การประชุมวิศวกรรมโยธาแห่งชาติ ครั้งที่ 28, 2023)
Flood is the primary natural hazard occurrence in Cambodia causing damage in both direct and indirect on majorities of development factor. Due to inadequate flood preparedness and mitigation, the damage estimation of flooding during historical extreme flood occurrences revealed significant damage to rice fields. The objective of this study was to estimate the damage value of rice over the whole country of Cambodia during the flood event in 2020. The flood map data in October 2020 through the World Food Program was used and overlaid with rice field map to generate rice damage map. The value of rice damage was estimated based on flood damage curve and average value of rice, showing value with different damage levels including 25%, 50%, and 100% damage. The resulting damage area was compared with government field-scale investigation and shown 66% consistency. From the result of this study are expected to support decision-making for better understanding of flood impact on rice to implement rice monitoring and update for planning to help mitigate damage impact and managing the restoration program over flood-vulnerable area after disaster.